Variations of Quality of Teacher–infant Interactions Across Play and Care Routine Activities - Cadima, Joana (2023)
This study examined the extent to which the quality of teacher-infant interactions varies across play and routine care activities. In addition, the effects of the quantity of adult involvement in the quality of teacher-infant interactions were investigated. Participants were teachers and infants from 90 infant classrooms in Portugal. Classrooms had, on average, six infants enrolled (M = 6.38, SD = 2.34), with the number of adults ranging from 1 to 3 (M = 2.00, SD = 0.60). Classrooms were observed by trained observers using the Classroom Assessment Scoring System–Infant (CLASS-Infant). Research Findings: Multilevel models showed that interaction quality varied as a function of type of activity. The quality of interactions of all CLASS domains was lower in routine care activities compared to play activities. Findings further showed that adult involvement was positively associated with all CLASS domains. In addition, after adding adult involvement to the models, differences between play and routine care activities were no longer statistically significant for most CLASS domains. Practice or Policy: Findings suggest the importance of considering the context of the activity and the levels of adult involvement when assessing and improving the quality of teacher infant interactions.